Peachpit Learning Series Mac OS X 10.5 Leopard - Williams, Robin (Peachpit Press, 2007)
Learn how to get the most out of Mac OS X version 10.5 Leopard with legendary teacher and a uthor Robin Williams. The Peachpit Learning Ser ies brings you the best-selling authors you know and love, on the topics that are near and dear to you, in a format that allows you to learn just what you need to know, and at your own pace. With this book, you can learn in your own way-whether it's working through the lessons from start to finish, jumping straight to step-by-step exercises about new features, or looking up just what you need to know at that moment. There are hundreds of exciting tools and hidden gems in your Macintosh. And with the gentle yet expert hand of Robin Williams guiding you along the way, you will learn to take full advantage of all that Leopard has to offer. If you are new to Mac OS X, you'll learn to use your Mac with help from a world-renowned teacher. From there, you can move on to customize it to suit the way you work. And if you've been using Mac OS X already, you'll learn to use the new features in Leopard, like Spaces, Quick Look, and Time Machine, and explore all the enhancements to favorites like Mail and iChat.
Online resource; Title from title page (viewed October 25, 2007)